Critical risk analysis swot rockslide underground mining operations - economica administrative unit Huachocolpa One - Alarcón M., E. César (2016)
This article seeks to identify weaknesses in preventing accidents caused by rockfall and thus innovate controls adequate to ensure that underground mining operations are carried out safely, fulfilling the strategic goals of production and safety risk the organization. What; This article serves as a reference document and application in the future in the medium term, the Administrative Huachocolpa One of Compania Minera Kolpa SA, Economic Unity develop its various mining operations in underground without accidents, thus ensuring that the most valuable resource of any organization; staff return safely to their homes every day.